Jazz and Blues Musicians of South Carolina : Interviews with Jabbo, Dizzy, Drink, and Others - Franklin, Benjamin, 1939- (Book collections on Project MUSE., 2008)
South Carolina has been home to an impressive number of regionally, nationally, and internationally known jazz and blues musicians. Through richly detailed interviews with nineteen South Carolina musicians, jazz historian and radio host Benjamin Franklin V presents an oral history of the tradition and influence of jazz and the blues in the Palmetto State. --from publisher description.